EFL Instructors’ Majors and Their Speaking Activity Choices for Informal Oral Assessment - Akdemir, Ahmet Selçuk; Ilhan, Berk (My University, 2019)
The purpose of the study is to investigate frequently used speaking tasks in English classes at tertiary level in Turkey and differences in language instructors’ speaking activity choices for informal oral assessment with regard to their academic majors. As data collection tool, an electronic questionnaire was sent to 82 participant language instructors from different universities in Turkey in the academic year 2016-2017. The questionnaire included speaking activities that can be used with assessment purpose and the participants were asked to report the frequency of the activities they used. The data which was collected through the electronic questionnaire was analysed by using SPSS 22 software. Kruskal-Wallis test revealed statistically significant differences between participants’ academic majors and speaking activities they used for informal oral assessment. Seven oral assessment activities were found to differ in frequency according to academic majors; picture-cued tasks, giving instructions/directions, role-play, discussions/conversations, games, picture-cued storytelling, and retelling story/news event. The differences were compared by mean ranks and medians, and these differences were classified according to the creativity the task required. In the light of the findings, practical and theoretical implications are given with concluding remarks.
Keywords: Eğitim; Eğitim Araştırmaları